Optimization of Academic Writing Through Zotero Training at the Faculty of Islamic Economics and Business IAIN Palangka Raya - Kuswaya, Adang; Tarantang, Jefry; Malisi, Muhammad Ali Sibram; Qalyubi, Imam; Sapuadi; Kasim, Helmy (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2022)
Academic writing at the Faculty of Economics and Islamic Business IAIN Palangka Raya has not been optimal, of course, due to several factors, one of which is that there are still many lecturers who do not understand the importance of citations. teaching to students in academic writing is also weak, even citations in academic works of both lecturers and students are not open source. For this reason, the activity or solution that will be carried out is in the form of training. The method used in this training program is to use service learning so that lecturers and students are able to improve soft skills in academic writing through the zotero application, which is carried out in 3 stages, namely the preparation stage, the serving stage, and the reflection stage. In the first stage, the team coordinated on optimizing academic writing through the zotero application, designing, formulating academic writing activities through the zotero application, and the team conducting socialization of academic writing using the zotero application. The second stage, the service, is holding academic writing training through the zotero application for lecturers and students. The third stage, reflection. In this stage, the team evaluates academic writing through the zotero application. The results of the implementation of academic writing through the zotero application at FEBI IAIN Palangka Raya are considered to improve performance, quality makes it easier and supports effectiveness in producing academic works that are in accordance with national and international citations that are scientifically and academically recognized. This activity greatly affects the quality of the FEBI IAIN Palangka Raya quality which is required to be able to produce quality academic works and an effective and efficient writing process, so that the goals of the vision and mission of FEBI IAIN Palangka Raya can be achieved.